Subcellular Dissection of a Simple Neural Circuit: Functional Domains of the Mauthner-Cell During Habituation - Bátora, Dániel; Zsigmond, Áron; Lőrincz, István Z.; Szegvári, Gábor; Varga, Máté; Málnási-Csizmadia, András (Frontiers in Neural Circuits, 2021)
Sensorimotor integration is a crucial feature of all nervous systems and ensures coordinated motor response for external stimuli. In essence, such neural circuits can optimize behavioral performance based on the saliency of environmental cues. In zebrafish habituation of the acoustic startle response is a simple behavior integrated in the startle command neurons, called the Mauthner cells. Whereas the major neurons participating in the startle response have been identified, it is still not well understood how the integration of distinct neuronal signals between the subcellular regions of the Mauthner cell regulate the behavioral performance. Here, we reveal mechanistically distinct dynamics of excitatory inputs converging onto the lateral dendrite and axon initial segment of the Mauthner cell by in vivo imaging glutamate release using iGluSnFR, an ultrafast glutamate sensing fluorescent reporter. We find that modulation of glutamate release by NMDA receptors is restricted to the axon initial segment, responsible for setting the sensitivity of the startle reflex and inducing a depression of synaptic activity during habituation. In contrast, glutamate-release at the lateral dendrite is not regulated by NMDA receptors, and serves as a baseline component of Mauthner cell activation. Finally, using in vivo calcium imaging at the feed-forward interneuron population component of the startle circuit, we reveal that these cells indeed play pivotal roles in both setting the startle threshold and habituation by modulating the axon initial segment of the Mauthner cell. These results indicate that a command neuron may have several functionally distinct regions to regulate complex aspects of a behavior.